2014
DOI: 10.1007/s11104-014-2214-6
|View full text |Cite
|
Sign up to set email alerts
|

The intercropping cowpea-maize improves soil phosphorus availability and maize yields in an alkaline soil

Abstract: Aim: This study assessed whether growing cowpea can increase phosphorus (P) availability in the rhizosphere and improve the yield of legume-cereal systems. In alkaline Mediterranean soils with P deficiency, it is assumed that legumes increase inorganic P availability.Methods: A field experiment was conducted at the Staoueli experimental station, in Algiers province, Algeria, to compare the growth, grain yield, P availability, and P uptake by plants with sole-cropped cowpea (Vigna unguiculata L. cv. Moh Ouali) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

16
77
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 128 publications
(99 citation statements)
references
References 32 publications
16
77
0
1
Order By: Relevance
“…The positive effect of N-TotalR on disease severity could be attributed to changes in soil pH. It has been demonstrated that N fixation can increase P availability in the rhizosphere through rhizosphere acidification mechanisms resulting from an increase in H + protons by nodulated roots, organic acids or acid phosphatases (Latati et al, 2014). Our results corroborate previous findings reporting a significant increase of disease severity in association to N availability in the rhizosphere (Shuga et al, 1994;Rao and Krishnappa 1996).…”
Section: Discussionsupporting
confidence: 91%
“…The positive effect of N-TotalR on disease severity could be attributed to changes in soil pH. It has been demonstrated that N fixation can increase P availability in the rhizosphere through rhizosphere acidification mechanisms resulting from an increase in H + protons by nodulated roots, organic acids or acid phosphatases (Latati et al, 2014). Our results corroborate previous findings reporting a significant increase of disease severity in association to N availability in the rhizosphere (Shuga et al, 1994;Rao and Krishnappa 1996).…”
Section: Discussionsupporting
confidence: 91%
“…Thus, soil bioavailable P could be defined as the potential supply of available P released from the soil by the rhizospheric processes of plant roots and microbes (Comerford, ). Four potential mechanisms of P acquisition by plants can be generalised: (a) root interception and diffusion of the soluble inorganic P pool that is easily available to the plants via root morphology modifications and mycorrhizal formations (Bolan, ), (b) organic acid complexation and dissolution of the active inorganic P pool that sorb onto clay particles or weakly bind to iron (Fe) or aluminium (Al) precipitates through organic acid exudation (Giles et al, ; Grinsted, Hedley, White, & Nye, ), (c) enzymatic hydrolysis of the labile organic P pool by phosphatase and phytase exudation (Fatemi, Fernandez, Simon, & Dail, ; Giles et al, ), and (d) H + /OH − /HCO 3 − extrusion of the occluded inorganic P pool that is used with difficulty by plants through H + /OH − /HCO 3 − exudation (Hedley et al, ; Latati et al, ) in the rhizosphere by plant roots and soil microbes. Deluca et al () proposed an extraction method that emulates the above four mechanisms through the use of four extractions (CaCl 2 , citric acid, phytase and phosphatase, and HCl) in parallel along a P lability to recalcitrant gradient and defined the four forms of bioavailable soil P as CaCl 2 ‐P, citric‐P, enzyme‐P and HCl‐P, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Most previous studies on cereal-legume intercropping assume implicitly that P and N acquisition by the cereal improves because the legumes are able to mobilize large amounts of P and N compounds [9,12]. Mechanisms that help to alter the rhizosphere processes of both intercropped species have been described [13], including mechanisms affecting soil nutrients availability.…”
Section: Introductionmentioning
confidence: 99%
“…Mechanisms that help to alter the rhizosphere processes of both intercropped species have been described [13], including mechanisms affecting soil nutrients availability. Indeed, cereal-legume intercropping can stimulate rhizosphere acidification through proton release by roots of N 2 -fixing legumes [8,12]. In contrast, alkalization can also enhance rhizosphere P availability in noncalcareous soils [9,14].…”
Section: Introductionmentioning
confidence: 99%